Ninth International Conference on Information Visualisation (IV'05)
DOI: 10.1109/iv.2005.117
|View full text |Cite
|
Sign up to set email alerts
|

Smart and Physically-Based Navigation in 3D Geovirtual Environments

Abstract: This paper describes an approach for smart and physically-based navigation, which aims at supporting effective and intuitive user interactions with 3D geovirtual environments (GeoVEs). The approach is based on two aligned concepts: 1) All navigation techniques are controlled by constraints that ensure user orientation and avoid "getting lost" situations. 2) All navigation techniques are handled in a time-coherent way achieving steady, continuous user movements using a physically-based motion model. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…When the angular distance between movement vector and view vector becomes large, the view returns to pointing forward. In addition, the assisted camera could support orientation (Buchholz, Bohnet, and Döllner, 2005;Kiss and Nijholt, 2003). When the camera is elevated, this scheme automatically orients the camera slightly downwards, in order to avoid filling the view with sky.…”
Section: Maintaining Orientationmentioning
confidence: 99%
“…When the angular distance between movement vector and view vector becomes large, the view returns to pointing forward. In addition, the assisted camera could support orientation (Buchholz, Bohnet, and Döllner, 2005;Kiss and Nijholt, 2003). When the camera is elevated, this scheme automatically orients the camera slightly downwards, in order to avoid filling the view with sky.…”
Section: Maintaining Orientationmentioning
confidence: 99%
“…First and foremost, users like the general idea of displaying the Earth in three dimensions, as they indicated they enjoyed viewing the Earth as it truly is. However, they noted that the interaction with a 3D environment was difficult and many expressed a desire for easier-to-control interfaces [7]. Finally, and most critically, over the half of the users indicated that they felt that virtual globes could be more useful to them if they only could figure out more tasks to perform with them (besides those they indicated).…”
Section: Design Requirementsmentioning
confidence: 99%
“…When selecting an organ a localization transition is triggered and moves the camera along a bounding sphere. Buchholz et al [4] discuss a constraint-based framework for navigation in virtual 3D landscapes.…”
Section: Guided Navigationmentioning
confidence: 99%